PENGARUH KEDALAMAN PADA OUTPUT FACTOR LAPANGAN KECIL DENGAN DETEKTOR THERMOLUMINESENSE DOSIMETER RODS DAN IONIZATION CHAMBER EXRADIN A16 - Laras Ati Nur Fatimah; Andrian Dede Handika; Wahyu Edy Wibowo; Supriyanto Ardjo Prawiro (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Radiotherapy with modern technique is a new choice of accurate and precision radiation therapy. Modern radiotherapy done with the used of small field to shape the field that conform with the volume target. The use of small field related with the treatment planning system (TPS) that assure the treatment delivery correspond with the prescribe dose. Small field is a field with a size less than the lateral range of their charge particles. This condition enable to produce a perturbation of the dose. Commissioning is early procedure to provide machine data to calculate the dose in TPS. The important step is output factor measurement. Output factor important to make sure TPS calculate accurate dose. This research shows output factor measurement with thermoluminesense dosimeter (TLD) LiF an ionization chamber Exradin A16. Radiation field size was 10x10 cm²; 4x4 cm²; 2.4x2.4 cm²; and 0.8x0.8 cm² was used with the solid water phantom measurement. The result then compared with the calculation of  TPS Pinnacle³. The result shows, the decrease of field size, the decreased of the dose output. The output factor measurement with Exradin A16 shows lower discrepancies than the TLD measurement. The result compared with the extrapolation data of the TPS.Keywords: output factor, small field, radiotherapy, Exradin A16, Thermoluminesense Dosimeter.